Total synthesis of (±)-simonsol C using dearomatization as key reaction under acidic conditions - Bi, Xiao-Yang; Yang, Xiao-Shuai; Chen, Shan-Shan; Sui, Jia-Jun; Cai, Zhao-Nan; Chuan, Yong-Ming; Qin, Hong-Bo (Beilstein Journal of Organic Chemistry, 2025)
The total synthesis of (±)-simonsol C was accomplished using a dearomatization under acidic conditions as key step to construct an aryl-containing quaternary center. The 6/5/6 benzofuran unit was formed through reductive elimination with Zn/AcOH and a spontaneous oxy-Michael addition. This synthesis consists of 8 steps and achieves an overall yield of 13%, making it the shortest known route.
Keywords: acidic dearomazation; benzofuran; (±)-simonsol C; total synthesis